National Needs Assessment for a Pediatric Trauma Toolkit: General Requirements for Moderate- and High-Volume Hospitals. Issue 6 (November 2021) - Cassidy, Laura D.; Benett, Sarah; Marion, Erica; Nichols, Lisa; Burke, Rita; Gray, Lisa; Morrell, Patricia; Schwing, Lisa; Waunch, Amy; Haley, Kathy
Abstract : Background: Optimal outcomes have been reported for children treated at pediatric trauma centers; however, most children are treated at nonpediatric trauma centers or nonpediatric general hospitals. Hospitals that are not verified or designated pediatric trauma centers may lack the training and level of comfort and skill when treating severely injured children. Objective: This study focused on identifying common pediatric guidelines for standardization across all trauma centers to inform a pediatric trauma toolkit. Methods: A needs assessment survey was developed highlighting the guidelines from an expert committee review. The purpose of the survey was to prioritize needed items for the development of a pediatric trauma toolkit. Professional trauma organizations distributed the survey to their respective memberships to ensure good representation of people who care for traumatically injured children and work in trauma centers. Deidentified survey results were analyzed with frequencies and descriptive statistics provided. Data were compared by hospital trauma verification level using a chi-square test. The value of p < .05 was considered statistically significant. Results: A total of 303 people responded to the survey. The majority of respondents reported a high value in the creation of a pediatric trauma toolkit for the guidelines that were included. There was variability in the reported access to the guidelines, indicating a significant need for the toolkit development and dissemination. Conclusion: As expected, Level III centers reported the largest gaps in access to standardized pediatric guidelines and demonstrated high levels of interest and need.